3
$\begingroup$

I have this here:

Find the interval on which $\displaystyle \sum_{n=0}^{\infty}\frac{x^n}{n+3}$ is convergent and use the geometric series to find the sum of the series.

I already found the interval of convergence. It's $[-1,1)$. That wasn't too bad.

How do I use the geometric series to find the sum though? I know that $\displaystyle \sum_{n=0}^{\infty} x^n=1+x+x^2+x^3+...+x^n=\frac{1}{1-x}$ and I have to differentiate and integrate $\displaystyle \sum_{n=0}^{\infty}x^n$ as needed until it looks like $\displaystyle \sum_{n=0}^{\infty}\frac{x^n}{n+3}$ but how can I manipulate the $\displaystyle \sum_{n=0}^{\infty}x^n$ ? I am 99% sure I have to integrate in some way and shift indices but I am not sure.

Any help would be great!

$\endgroup$
4
$\begingroup$

We have $$\frac{1}{1-x}=\sum_{n=0}^\infty x^n$$ and $$\frac{x^2}{1-x}=\sum_{n=0}^\infty x^{n+2}$$ by integrating $$\int\frac{x^2}{1-x}dx=\sum_{n=0}^\infty \int x^{n+2}dx\\ =\sum_{n=0}^\infty\frac{x^{n+3}}{n+3}\\ =x^3\sum_{n=0}^\infty\frac{x^{n}}{n+3}$$

$\endgroup$
1
  • $\begingroup$ I follow what you did but the multiplication of the $x^2$ is something that I didn't expect to do haha. That's cool! $\endgroup$ – Future Math person Feb 25 '20 at 7:55
3
$\begingroup$

If $f(x) = \sum\limits_{n=0}^{\infty} x^{n+2}$ then $\int_0^{x} f(t) dt= \sum\limits_{n=0}^{\infty} \frac {x^{n+3}} {n+3}=x^{3}\sum\limits_{n=0}^{\infty} \frac {x^{n}} {n+3}$. Can you continue from here?

$\endgroup$
1
  • $\begingroup$ Yes I got it :) . It just seems unintuitive to just start from there. Thanks! $\endgroup$ – Future Math person Feb 25 '20 at 7:55
2
$\begingroup$

$$S=\sum_{n=0}^{\infty}\frac{x^n}{n+3}\implies(x^3S)=\sum_{n=0}^{\infty}\frac{x^{n+3}}{n+3}\implies(x^3S)'=\sum_{n=0}^{\infty}{x^{n+3}}=x^3\sum_{n=0}^{\infty}{x^{n}}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.